Predictors of body image dissatisfaction in kinesiology students - Jakobek, Vedran; Kranjčev, Mislav; Barić, Renata (Frontiers in Psychology, 2024)
This research aimed to examine predictors of discrepancies between actual and ideal body images, specifically body fat and muscularity discrepancies, in Kinesiology students. Volunteer participants (N = 174, men = 112, women = 62) filled out the sex-specific Somatomorphic Matrices (NSM-M and SM-F) as well as The Positive and Negative Perfectionism Scale (PNPS), Rosenberg Self-esteem Scale (RSE), and the Eating Attitudes Test (EAT-26) using paper and pencil tools. The median and Mann-Whitney U tests were used to determine sex differences, and regression analyses were used to determine the contribution of sex, perfectionism, self-esteem, and eating attitudes in explaining the variances in body fat and muscularity dissatisfaction. The results showed no sex differences in body fat discrepancy, while men showed more discrepancy between actual and ideal muscularity than women. In regression analyses, sex was the only significant predictor of muscularity discrepancy, while disordered eating attitudes were a positive, and positive perfectionism was a negative predictor of body fat discrepancy. This study showed that while muscularity dissatisfaction is linked to male sex, body fat dissatisfaction is not related to sex, but to psychological variables of disordered eating attitudes and positive perfectionism, in a population of youths that may be above average when it comes to physical activity.